2023
DOI: 10.1111/apa.16722
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioural outcomes at 8 years of age in preterm‐born children: A longitudinal study

Abstract: Prematurity has been well recognised as a risk factor for adverse functional outcomes, including motor, cognitive, emotional and behavioural problems. 1,2 Several studies have highlighted the longterm risks of 'high-prevalence and low-severity' disabilities such as learning disorders and behavioural problems for preterm children when reaching childhood. 3 Besides, preterm children present a specific pattern of behavioural characteristics that consists of inattention, emotional and socialisation difficulties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Considering gestational age at delivery, a recent article shows a potential link between preterm birth and emotional symptoms during childhood ( Tsakalidis et al, 2023 ). It was also found that cytokine dosages in cord blood differed between preterm and term infants ( Anderson et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering gestational age at delivery, a recent article shows a potential link between preterm birth and emotional symptoms during childhood ( Tsakalidis et al, 2023 ). It was also found that cytokine dosages in cord blood differed between preterm and term infants ( Anderson et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%